(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to fintd out the degree of availability of Mathematical Coherence skills among teachers mathematics in the city of lattakia in the first semcster of the academic year (2020)CE. The research used direct observation as atool to verify the Mathematical Coherence skills of teachers mathematics. He identified Four grades (larqe-medium- weal, anolvery). The seale (4-3-2-1) was determined for these scerses. Respetively. The positivistic approoch was used forits suibility for the purposes of the research, as the namber of sample memeers was (28) teachers, the research , the research resulted in the availability of Mathematical Coherence skills among teachers to amederate degree the research presented anunrbers of proposals that contribute to achieving the Mathematical Coherence skills of teachers of mathematics.